2004
DOI: 10.1007/s00441-003-0811-4
|View full text |Cite
|
Sign up to set email alerts
|

Calbindin-D9k (CaBP9k) localization and levels of expression in trophoblast cells from human term placenta

Abstract: During pregnancy, the calcium (Ca(2+)) transport machinery of the placenta is solely responsible for the nutrient supply to the developing fetus, where active Ca(2+) transport occurs from the mother to the fetus. As part of a larger study to determine the role of Ca(2+) in placental transport in vivo, we questioned whether calbindin-D9k (CaBP9k), which is mainly expressed in duodenum, uterus, and placenta of several mammals, is present in cytotrophoblast cells and syncytiotrophoblasts of human term placenta. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…In the present study, cultured syncytiotrophoblast cells expressed the mRNAs of calbindin-D 9k and calbindin-D 28k , which confirm the results obtained by Belkacemi et al [12,13], who have reported the presence of the mRNA and protein of both calbindins in cultured human placenta cells. The effects of calcitriol on calbindins gene expression have not been evaluated in human placenta.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In the present study, cultured syncytiotrophoblast cells expressed the mRNAs of calbindin-D 9k and calbindin-D 28k , which confirm the results obtained by Belkacemi et al [12,13], who have reported the presence of the mRNA and protein of both calbindins in cultured human placenta cells. The effects of calcitriol on calbindins gene expression have not been evaluated in human placenta.…”
Section: Discussionsupporting
confidence: 95%
“…Regarding calbindin-D 9k , we did not find information about its relation with lipid peroxidation. Interestingly, calbindin-D 9k and calbindin-D 28k have been found in cultured trophoblast cells [12,13]. In addition, it has been reported that calcitriol stimulates calbindin-D 28k mRNA and protein in human choriocarcinoma cell line JEG-3 [14].…”
Section: Introductionmentioning
confidence: 97%
“…Over the last third of gestation, gene and protein expression for calbindin-D 9K increases markedly in both mouse and rat placenta Glazier et al, 1992;Hamilton et al, 2000;Mathieu et al, 1989) and correlates with the increase in unidirectional maternofetal 45 Ca clearance measured over the same period (Glazier et al, 1992), suggesting that transcytosolic transfer on this protein and the dynamic equilibrium between bound and free Ca 2+ in the syncytiotrophoblast might be the rate limiting step of transfer in these species. The situation may well be quite different in the human placenta where it has proved difficult to show the expression of calbindin-D 9K (Belkacemi et al, 2004), or to determine if another protein is involved instead. Interestingly, the activity, but not expression, of PMCA in the BM of human placenta increases linearly over the last third of gestation (Strid and Powell, 2000).…”
Section: Ca 2+ Transportmentioning
confidence: 99%
“…Among these, the calbindin proteins, a family of cytoplasmic CBPs containing an EF-hand motif, have been extensively investigated. Thus, S100 calcium binding protein G (S100G), calbindin 1 (CALB1), and calbindin-57K (CaBP57K) have been detected in the human and murine trophoblasts [18,[21][22][23]. Furthermore, an increase in calbindins expression at term, as well as during trophoblastic differentiation, has been reported [18,21,23].…”
Section: Discussionmentioning
confidence: 92%